The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fonc.2020.00322
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulation by the Translation Machinery and Its Implications in Cancer

Abstract: Various metabolic pathways and molecular processes in the cell act intertwined, and dysregulating the interplay between some of them may lead to cancer. It is only recently that defects in the translation process, i.e., the synthesis of proteins by the ribosome using a messenger (m)RNA as a template and translation factors, have begun to gain strong attention as a cause of autophagy dysregulation with effects in different maladies, including cancer. Autophagy is an evolutionarily conserved catabolic process th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 101 publications
(103 reference statements)
0
35
0
Order By: Relevance
“…3A, B). Many autophagy inducers require eIF2α phosphorylation as a mandatory step for the ignition of the process 48 . Accordingly, we observed that a knockin mutation that renders eIF2α non-phosphorylatable (due to the replacement of serine in position 51 by an alanine residue: genotype eIF2α S51A/S51A ) strongly inhibited the induction of GFP-LC3 puncta by AZT, CQ, and HCQ ( Fig.…”
Section: Lysosomotropic Agents Induce Eif2a Phosphorylation In Vitromentioning
confidence: 99%
“…3A, B). Many autophagy inducers require eIF2α phosphorylation as a mandatory step for the ignition of the process 48 . Accordingly, we observed that a knockin mutation that renders eIF2α non-phosphorylatable (due to the replacement of serine in position 51 by an alanine residue: genotype eIF2α S51A/S51A ) strongly inhibited the induction of GFP-LC3 puncta by AZT, CQ, and HCQ ( Fig.…”
Section: Lysosomotropic Agents Induce Eif2a Phosphorylation In Vitromentioning
confidence: 99%
“…The main objective of autophagy or “self-eating” (Greek meaning) is to break down cytoplasmic components like macromolecules and organelles, in order to sustain cellular metabolism and to ensure cellular homeostasis [ 16 , 38 , 39 ]. Some people described autophagy as a cellular “re-cycling process” that digests old and unwanted substances and turns it into useful nutrients for cellular usage [ 25 ].…”
Section: Autophagy Types and Process And Functional Roles Of Autophamentioning
confidence: 99%
“…Some people described autophagy as a cellular “re-cycling process” that digests old and unwanted substances and turns it into useful nutrients for cellular usage [ 25 ]. Autophagy is important to avoid the accumulation of harmful substances like precipitated proteins, damaged cellular organelles and oncogenic materials that could pose danger to the cells [ 38 , 39 ]. The failures to eliminate these unnecessary, aged or toxic substances would trigger intracellular inflammation which would generate reactive oxygen species (ROS) and subsequently, these cellular processes would lead to the development of cellular degeneration, apoptosis and carcinogenesis [ 38 – 40 ].…”
Section: Autophagy Types and Process And Functional Roles Of Autophamentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is besides apoptosis another catabolic pathway essential in homeostasis of cells [ 125 ]. Both mechanisms are interconnected by several molecular nodes and a close cross-talk exists [ 54 ].…”
Section: Vault Rnas and Autophagymentioning
confidence: 99%